'Now I see how my students feel': expansive learning in a language awareness workshop. Issue 3 (2nd July 2016) - Fajardo, Guadalupe Ruiz; Torres-Guzmán, María E.
ABSTRACT: This study looks at a case study research on a language awareness workshop in a New York public school with a dual language (Spanish/English) program. A learner-centred lesson, taught in Spanish, focused on basic personal information exchanges for in-service teachers who taught only in English and who had some limited knowledge of Spanish. The instructors' charge was to teach participants how to exchange basic personal information in Spanish. Working from a cultural historical activity theory perspective, the interactions that took place in a videotaped session were analysed, using tools from discourse analysis, conversation analysis, and linguistics. The focus was set on the interactions of the instructors with one of the teachers in the workshop to examine how she moved from resisting a new language to embracing an understanding of the role of a new language in learning by paying attention to the dynamics of identity production. By exploring moment-to-moment identity moves and moves across time, the authors identified learning actions leading to the potential of expansive learning and suggesting enhancement of the concept of experiencing (Sannino, 2010 ) by examining the production of the teacher's identity.